Chitotriosidase, a marker of innate immunity, is elevated in patients with primary breast cancer - Thein, Mya Sanda (2017)
BACKGROUND:Cancer progression has been associated with altered immune cell function and activation. Neopterin, which is secreted by interferon-γ stimulated macrophages, exhibits an association with multiple cancer types and metastatic disease. Chitotriosidase, which is secreted by chronically activated macrophages and granulocyte-macrophage colony-stimulating factor stimulated neutrophils has not been studied in the setting of cancer.OBJECTIVE:The goal of this discovery study was to screen chitotriosidase for diagnostic capacity in detecting cancer and compare its operating characteristics with those of neopterin.METHODS:Serum from subjects with breast (n= 66) or prostate (n= 70) cancer, and from 204 subjects free of malignant disease were studied. Chitotriosidase was measured by enzyme activity assay, while neopterin was measured by a competitive enzyme immunoassay. Statistical analyses included group comparisons by Mann Whitney U test, diagnostic capacity by receiver operating characteristics (ROC) curve analysis and biomarker associations with physiologic and clinical measures by Spearman correlation.RESULTS:Chitotriosidase activity was significantly higher in both cancer types compared with gender matched controls, though only in breast cancer was the diagnostic capacity significant (area under the ROC curve of 0.97 ± 0.01). In contrast, neopterin was significantly elevated in prostate cancer and exhibited discriminatory capacity (area under the ROC curve of 0.76 ± 0.05). Age, BMI, % body fat and metastasis were variables that correlated with neopterin, but not chitotriosidase levels.CONCLUSIONS:The operating characteristics of serum chitotriosidase were different from neopterin and further analysis of chitotriosidase as a biomarker for breast cancer is warranted.